Inhibition of Xylocarpus granatum Extracts against the Growth of Pathogenic Bacteria (Pseudomonas aeruginosa, Escherichia coli and Vibrio alginolyticus) - Elkana Gabariel; Dessy Yoswaty; Nursyirwani Nursyirwani (Jurnal Perikanan dan Kelautan, 2019)
The research was conducted from October until Desember 2018 at the Laboratories of Marine Chemistry and Marine Microbiology, University of Riau and Integrated Chemical Laboratory, University of Muhammadiyah, Riau. The Purpose of this research was to determine the inhibition of Xylocarpus granatum extracts on the growth of pathogenic bacteria (P. aeruginosa, E. coli and V. alginolyticus). Samples used for were leaves, fruits, and rods extract of X. granatum  andthe extacts was preferred different at concentrations 100%, 50%, 25% and 12,5%. The result showed that  the highest concentration at 100 %, rod was the best extracts to against the growth of pathogenic bacteria and the antimicrobial compound could inhibit thr growth of pathogenic bacteria (P. aeruginosa, E. coli and V. alginolyticus) with intermediate ability with clear zone diameter between 0,3 – 10 m